Selective Vagus Nerve Stimulation as a Therapeutic Approach for the Treatment of ARDS: A Rationale for Neuro-Immunomodulation in COVID-19 Disease - Mastitskaya, Svetlana; Thompson, Nicole; Holder, David (Frontiers in Neuroscience, 2021)
Acute respiratory distress syndrome (ARDS) is the most severe form of acute lung injury. It is induced by sepsis, aspiration, and pneumonia, including that caused by SARS coronavirus and human influenza viruses. The main pathophysiological mechanism of ARDS is a systemic inflammatory response. Vagus nerve stimulation (VNS) can limit cytokine production in the spleen and thereby dampen any systemic inflammation and inflammation-induced tissue damage in the lungs and other organs. However, the effects of increased parasympathetic outflow to the lungs when non-selective VNS is applied may result in bronchoconstriction, increased mucus secretion and enhance local pulmonary inflammatory activity; this may outweigh the beneficial systemic anti-inflammatory action of VNS. Organ/function-specific therapy can be achieved by imaging of localized fascicle activity within the vagus nerve and selective stimulation of identified organ-specific fascicles. This may be able to provide selective neuromodulation of different pathways within the vagus nerve and offer a novel means to improve outcome in ARDS. This has motivated this review in which we discuss the mechanisms of anti-inflammatory effects of VNS, progress in selective VNS techniques, and a possible application for ARDS.